Diagnosis, monitoring and management of immune-related adverse drug reactions of anti-PD-1 antibody therapy - Eigentler, Thomas; Hassel, Jessica C.; Steins, Martin (Cancer treatment reviews, 2016)
PD-1 checkpoint inhibitors are associated with a specific spectrum of immune-related adverse events. This spectrum is different from toxicities known for kinase inhibitors or cytotoxic drugs. Since PD-1 directed therapies show effectivity in an increasing number of malignant diseases, their clinical usage will increase rapidly. Therefore clinicians from different specialities such as medical oncology, internal medicine, family doctors and emergency unit staff should be aware of the adverse effects of PD-1 checkpoint inhibitors to avoid delays in diagnosis and treatment. Based on pooled data from pivotal trials as reported by the European Medicines Agency, the present paper reviews incidences and kinetics of onset and resolution of immune-mediated “adverse events of specific interest” (AEOSI) of both approved PD-1 inhibitors nivolumab and pembrolizumab. In general, the severity of AEOSI is mild to moderate (grade 1-2); the frequency of immune-mediated but also idiopathic grade 3-4 adverse drug reactions is ⩽2% for any event term. Recommendations for the diagnosis, monitoring and management of the relevant dermatological, gastrointestinal, pulmonary, endocrine, renal and hepatic toxicities are convened by an expert panel that consolidated and clarified treatment recommendations after the onset of AEOSI. Although the time of onset is not predictable - the medians range from 1 to 6months - the huge majority of events is reversible, with no impact of the time of onset. By the systemic use of glucocorticoids, notably methylprednisolone or equivalents, most AEOSI are well manageable. Non-steroidal immunosuppressants may be used in certain cases of refractory/recalcitrant, long-lasting immune toxicities. With regard to the outstanding clinical activity of the anti-PD-1 antibodies, therapy restart is the principal therapeutic option after recovery of grade 2 AEOSI, or diminution of higher grade skin or endocrine events to mild severity. Early diagnosis and close clinical monitoring are essential for successful management of immune-related adverse events.